2002
DOI: 10.1103/physreva.66.021801
|View full text |Cite
|
Sign up to set email alerts
|

Extreme-ultraviolet high-order harmonic pulses in the microjoule range

Abstract: We study high-order harmonic generation at a high pumping energy using a long focal length lens. We identify different saturation regimes of the harmonic emission, revealing the interplay between phase matching, absorption, and laser defocusing. In the optimal conditions, high conversion efficiencies are obtained, resulting in an increase of at least one order of magnitude of the harmonic energies compared to previously reported values. In xenon, microjoule energies are reached, opening new perspectives for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(120 citation statements)
references
References 27 publications
3
114
0
3
Order By: Relevance
“…Averaging the results of 10 single shot energy/efficiency records, a value of η XUV ≃ (3.7 ± 1.0) × 10 −4 for = 17-80 nm was obtained. This is comparable or even higher than that of gas harmonics [3][4][5][6].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Averaging the results of 10 single shot energy/efficiency records, a value of η XUV ≃ (3.7 ± 1.0) × 10 −4 for = 17-80 nm was obtained. This is comparable or even higher than that of gas harmonics [3][4][5][6].…”
Section: Resultsmentioning
confidence: 89%
“…However, due to intrinsic processes associated with this generation mechanism, there is a maximum laser pulse intensity that can be used with the consequence of limiting their brightness and severely restricting the scope of applications [2,3]. Techniques like the loose-focusing [4][5][6][7] or the double optical gating [8] have been implemented to enhance the XUV flux and exploit higher laser energies from modern laser systems. More recently using these techniques, a tabletop source delivering 2.6 GW power in a single attosecond pulse was reported [9].…”
Section: Introductionmentioning
confidence: 99%
“…In set up I we used a gas jet as the HHG medium. The focal length of the lens, the laser pulse energy, the numerical aperture of the laser at the lens position, the length of the rare gas generation medium along the laser propagation axis and the gas medium pressure need to be optimized for a given generation gas to reach maximum VUV flux (1,2,4,(8)(9)(10)(11)(12)(13)(14).…”
Section: Experimental Set Up I and Results: Spectral Characteristmentioning
confidence: 99%
“…Often, the technological and methodological challenges for the generation and application of attosecond pulses are very different from those for femtosecond pulses. As we are describing our approach with femtosecond resolution we shall concentrate in the following on femtosecond pulses from High Harmonic Generation (HHG) (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The applications of such pulses range from spectroscopy (1,2,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) to microscopy (28,29) and coherent diffraction or holography (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental efforts in this time scale have been restricted to XUV-IR pump-probe schemes [1][2][3][4][5][6][7] or in situ electron-ion collision methods [8]. Systematic developments in highpulse-energy HHG [9][10][11][12][13] and XUV supercontinua [14][15][16][17][18][19] paved the way to time-delay spectroscopic studies [20] and XUV-pump-XUV-probe experiments [21,22] that have lately demonstrated their first proof-of-principle application in the measurement of induced, ultrafast evolving atomic coherences in an atomic continuum [20,22]. Such measurements are free of interventions from unwanted channels, opened through quasiresonant multi-IR-photon transitions.…”
Section: Introductionmentioning
confidence: 99%